This is a rooster. This is a novella? A challenge to the traditional classification of "El curioso impertinente" - Gordon, Michael (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Critical studies of “El curioso impertinente” have ignored, perhaps because it seemed obvious to do so, one fundamental aspect of this intercalated novella with respect to the work within which it is found; that is to say, its genre. Iffland (1987) summarizes the countless ambiguities found throughout Don Quixote to conclude that this book is unique in its contradictoriness, and I argue that what happens with respect to the genre of “El curioso” is merely a symptom of what plagues the larger work. Therefore, I simultaneously propose in this article a questioning of the definitive classification of “El curioso” and an argumentation in favor of it being considered a type of early, shorter chivalric romance. As happened with Orbaneja’s painting of the rooster (II, 3), just because “El curioso” is defined as a novella, that does not mean that it is or that it cannot be interpreted as something else. “El curioso” shares the three fundamental characteristics of early 16th-century chivalric romances (i.e., form, finality, and subject) identified by Lucía Megías y Sales Dasí (2008), and therefore, it behaves as if it were cut from the same cloth.